Influence of Tribal Development Rubber Planting Project on the Socio-Economic Status of the Kani Tribes of Nedumangad Taluk, Thiruvananthapuram - HariKumar K (Department of Plantation Crops and Spices, College of Horticulture, 1997)
The study was conducted among the beneficiaries of Tribal Development Rubber Planting Project, a collaborative project of Rubber Board and Department of Scheduled Tribe Development, Government of Kerala, implemented in the seven tribal settlements of Nedumangad taluk of Thiruvananthapuram district for a period of five year from 1989 to 1993. The study was aimed at assessing the extent of increase in the economic condition of the tribals. The impact of the project on the socio – economic progress of the settlement and the extent of adoption of scientific rubber planting and maintenance techniques by the tribal were also studied. One hundred and five beneficiaries inhabiting the different TDRPP implemented settlements were interviewed with the help of a pre tested questionnaire. The study revealed that the project was able to bring 16.8 per cent of the total tribal families in the district and 66.05 per cent of the Kani families in the TDRPP implemented settlement in to rubber cultivation. This was a great achievement in a short span of five years. The target area envisaged in the project was also achieved. There was improvement in the soil conservation measures adopted also. Ninety five per cent of the tribals adopted soil conservation measures in their plantation after implementation of the project. One of the objectives of the project was to improve the economic status of the tribes. The study revealed that eventhough the plantations have not reached the yielding stage, the economic status of the tribes have shown improvement. This indicates that the implementation of TDRPP has not affected their daily income earning works and cultivations. Moreover, they got income from additional labour obtained and also from sale of cover crop seeds, rubber seeds and intercrops. The average per hectare production of cover crop seeds was found to be a little higher than the average quantity projected by the Rubber Board. The collection of rubber seeds seems to be unimpressive. As against 250 kg/ha production of rubber seeds from normal healthy rubber plantations, the production in the TDRPP implemented settlements was ranging from 6.54 kg to 38.94 kg per hecter per year. The study revealed that only 83 beneficiaries carried out intercropping during the first year of plantation. The number reduced to 44 and 10 in the second and third year of planting, respectively. This indicated that the area in the rubber plantation has not been properly utilized for earning incomes from intercrop. From the study it was found that the tribals were not getting the actual market price for their produce. The majority of the tribal beneficiaries were casual labourers on daily wages or forest produce gatherers. The employment potential generated by the project has been utilized by the tribals significantly. They have obtained 34 to 46 mandays of additional labour per year without any suffering to their routine works. This has produced an additional income of Rs.2550 to 3450 in a year. The most significant advantage of the project was the skill acquired by the tribals on different aspects of maintenance of rubber plantation. The study showed that 73.2 per cent of the beneficiaries learned the pitting and refilling techniques for planting polybag plants. The skill of planting of polybag plants was acquired by 81.2 per cent of the beneficiaries. Skills for terracing work in rubber plantation, branches induction in the young plants, manuring and operation were acquired by the tribal beneficiaries by 77.6, 81.9 and 79.7 per cent, respectively. Another significant observation obtained during this study was that the educational status of the tribal beneficiaries has inversely proportional to the skill acquired. Majority of the tribals approved the mode of implementation of the scheme. The results also showed that implementing developmental projects in the same lines will provide over all benefits to the tribals. The majority of the beneficiaries strongly refuted the statement of decrease in the area for the cultivation of annual crop due to the implementation of the project. The implementation of the project has provided a feeling on the tribal sect that they are one among the rubber cultivaters in the locality which tempt to discard the social insecurity feeling among them. Due to this feeling, majority of the tribals agreed to change their life style according to the additional income they got from this scheme. The level of aspiration (future) also confirm this aspect. Conclusion The study lead to the following conclusions. 1. The socio-economic condition of tribal beneficiaries in the Tribal Development Rubber Planting Project implemented settlements showed improvements. Thus the main objective of the project was successfully achieved. 2. In contrast to the previous development programmes in the tribal areas, the extent of rubber cultivation in the country has been physically enhanced. 3. The mode of implementation was found to be very effective and in addition to uplifting the tribals economically, the procedure has helped them to acquire various skills. 4. Guidance should be provided for maximum utilization of area in the plantation for raising intercrops in the first three years as recommended by the Rubber Board. 5. Infrastructure facilities should be provided by the Governmental or voluntary organisations to the tribals to get the maximum available market price for their produce. Rubber processing facilities should be immediately provided in project area as envisaged in the programme. 6. Proper training should be imparted to higher education categories to develop skill in various works.